Efficacy of a Web-Based Intervention (Smart Choices 4 Teens) for Facilitating Parent-Adolescent Communication About Relationships and Sexuality: Randomized Controlled Trial - Bourdeau, Beth (JMIR Pediatr Parent, 2021)
BACKGROUND: There is a need for interventions that promote healthy decision making among adolescents and leverage the ongoing impact of parental relationships through older adolescence and young adulthood. These interventions should maximize adolescent engagement and be easily accessible to families in terms of cost, duration, and logistics related to participation. OBJECTIVE: This study aims to test the efficacy of the healthy relationships and sexual decision-making component of a web-based intervention for older adolescents and their parents, ascertain whether the efficacy varies by gender, and assess its efficacy over time. METHODS: A randomized controlled trial was conducted for the web-based, self-paced intervention Smart Choices 4 Teens from 2014 to 2015. Families (N=411) with adolescents aged 16-17 years were randomly assigned to the intervention or control condition. Surveys assessing aspects of sexual communication were administered at baseline and at 6, 12, and 18 months. Generalized estimating equations were used to determine the impact of exposure to the relationships component of the intervention on sexual communication by parents, as reported by adolescents. RESULTS: Less than half (88/206, 42.7%) of the intervention group participated in the third and final intervention component, which was focused on relationships and sexual decision making. Participation in the relationships component increased the frequency of parental sexual communication and increased the number of dating rules after accounting for other significant adolescent characteristics. The impact of the intervention varied little by gender, although it did demonstrate an impact on communication reports over the follow-up survey administrations. CONCLUSIONS: Smart Choices 4 Teens demonstrated efficacy in increasing the frequency of sexual communication between parents and adolescents in the long term. TRIAL REGISTRATION: ClinicalTrials.gov NCT03521115; https://clinicaltrials.gov/ct2/show/NCT03521115